Effects of the seaweed Caulerpa prolifera establishment on the biodiversity of Ria Formosa Lagoon - Parreira, Filipe Biscaia Gonçalves (2018)
Caulerpa prolifera (Forsskål) J. V. Lamouroux is an opportunistic green seaweed that is establishing on the unvegetated bottoms of Ria Formosa, often where seagrass meadows took place in the past. Ria Formosa is a coastal lagoon that extends along the southern Portuguese coast, place for a wealth of commercial and leisure activities. Such activities are supported, in the subtidal, by the important dominant seagrass communities which rank among the most valuable ecosystems on earth. The bottom of the lagoon is mainly constituted by unvegetated areas, seagrass meadows and C. prolifera meadows. For over than 170 years since the first report of this seaweed in Ria Formosa, its effect on the biodiversity has never been studied. In this study we aimed to understand how the establishment of C. prolifera on bare sediment in Ria Formosa affect the lagoon’s biodiversity. To do so we compare the plant and fauna assemblage between three habitats, one dominated by a continuous C. prolifera meadow, one dominated by a Cymodocea nodosa and Zostera marina mix meadow and one unvegetated bed. We address three main questions: 1) Does fauna and plant assemblages differ in abundance, biomass, species richness and diversity between habitats?, 2) Do the three habitats differ in the fauna assemblages of commercial valued species?, and 3) do they differ in nursery functions? Similar fauna diversity was found within vegetated habitats (C. prolifera and C. nodosa/Z. Marina dominated habitats), followed by unvegetated sediments. Bittium reticulatum and Loripes orbiculatus revealed to be good indicators for the differences found in the fauna assemblage and nursery function, where seagrass showed the highest nursery role. Differences in the assemblage of commercial valued species were marked by Upogebia spp. (“ralos”) presence in C. prolifera meadow, where the highest provision of habitat for commercial species was found.